Understanding the causes of injury: Implications for prevention - Mitchell, D.; Finch, C. (1999)
Over recent years there has been an increasing understanding of the importance of descriptive epidemiology of sports injuries in the general sporting community. Whilst the focus of this information has been on describing the incidence or prevalence of sports injuries, there is a need for epidemiological data about the etiology of these injuries. Strategies to prevent sports injuries need to be based on a detailed understanding of the causes. The time has come to begin asking the question 'why do these injuries occur?' rather than solely continuing to focus on the description of these injuries. The objective of this research is to describe the causes of injury as they occur in the sporting and recreational context. Relevant information was obtained from the Sports Medicine Injury Surveillance (SMIS) database. This database of 6476 new sports injury cases was collected through the five allied Sports Medicine Centres of Victoria (SMCV) within suburban Melbourne, Australia. The patients treated at these clinics represent individuals from a range of sporting backgrounds, from recreational participants to high level athletes. Data pertaining to cause of injury, sport associated with injury and site of injury was extracted from the database. The five most common causes of injury were overuse (24.8%), being struck or hit by another person (12.3%), awkward landings (11.0%), collisions with moving objects (10.8%) and twisting/rotational components (9.7%). Australian football, basketball and netball were highly associated across all five causal categories. For example, Australian football accounted for 14.4% of overuse injuries, 66.6% of incidents involving being struck or hit by a person, 22.6% of awkward landings, 57.3% of collisions with moving objects and 17.5% of cases caused by a twisting or rotational component. Overall, the knee was the most common site of injury in four of the five causal categories, while the ankle accounted for highest proportion of awkward landings (49.7%). A detailed analysis of the text narrative provides further insight into the causes of injury. Further investigation into these causes of sports injury, utilizing a collaborative approach between epidemiology and biomechanics could lead to the development of a causal model describing, in detail, how these injuries occur. The implication of this development is the subsequent modeling of a preventative strategy, to potentially reduce the risk of sports injury occurrence.